Primary School Social Studies Curriculum: Comparison of National Curriculum (NC) 2006 and Single National Curriculum (SNC) 2020 - Rabia; Waheed, Dr. Syed Abdul; Gilani, Dr. Nadia (University of Wah Journal of Social Sciences, 2023)
From the perspective of globalization and technological advancements, the change in social studies curriculum is deemed important because it provides the necessary knowledge, skills, competencies, and attitude toward the modern world and makes students responsible national and global citizens. This study aims to compare and find the differences between National Curriculum (NC) 2006 and the new Single Nation Curriculum (SNC) 2020 for the grade five Social Studies textbook. Content Analysis was employed to compare both the curricula of social studies. For this purpose, a rubric was developed to analyze the key differences between NC 2006 and SNC 2020 in terms of content, student learning outcomes, suggested activities, information other than textbooks, website links, assessments, and projects. Major findings of the content analysis revealed that information about the struggle of Quaid-e-Azam Muhammad Ali Jinnah, Allama Iqbal, and other prominent personalities in the creation of Pakistan was not found in the new curriculum. Website links are given at the end of each chapter to integrate the technology in the classroom for further information through different sites.